Processo de modelagem de informações em plataforma BIM e transferência de dados para certificação EDGE - Thaïs Ribeiro Molina (2020)
This research sought to develop a system based on Building Information Model (BIM) in order to structure requirements and provide information necessary for the (partial) data transfer requested by the online software of the Certification Excellence in Design for Greater Efficiencies (EDGE),. The achievement of this objective aims, ultimately,to make it possible to calculate the energy incorporated in the materials and systems used in the model, in an automated way. The methodology used was Constructive Research. The tools applied were Autodesk Revit, Dynamo, Excel and Python programming languages. Despite the use of proprietaries softwares, there were not any interoperability issues due to the compatibility of the systems applied. The proposed information modeling process enabled the removal of the model parameters required by the EDGE Certification, within the scope limits established in this project. The results obtained corroborate the potential of BIM technology to contribute to improving the performance of the building design process, with a view to environmental certification. It was identified that the various aspects of a building's performance, such as materials and energy resources, have been found to connect and affect each other. The automation of the system brought the possibility of verifying several design alternatives in a short time, keeping the information always updated and the reliable result. The contribution of this research to the academy and the market is to present an information modeling process that enables communication between a BIM model and an eco-efficiency certification. The result that the process returns is liable to be analyzed and evaluated by the agents involved for a more informed decision-making in relation to the impacts that the project produces on the environment.